Cableless battery charger using induction technique for electric vehicles - Mahmood, N. H.; Alias, M. A.; Mustapha, M. W.; Esa, M.; Taha, F. (2003)
Electromagnetic induction is the production of an electromotive force in a conductor as a result of a changing magnetic field about the conductor. The induced emf always such that it opposes the change that gives rise to it, according to Lenz's law. In our work, we are considering in controlling the magnetic flux distribution through an air-gap during the energy transfer from the source to load. This research has put a core situation in investigating the possible ways of charging the batteries via mutual induction as in transformers. This enables the charging process to be cableless. It involves two coils transferring energy from one to the other through air in the most efficient way. Our work is presented in this paper. Simulation and hardware implementation has been carried out successfully. We have measured the magnetic flux density for ac input voltage of 100 Volt with different frequency values. The optimum frequency in our design is 25 Hz. We found that it is possible to control the magnetic flux distribution during energy transmission by optimizing the frequency and shielding the flux path.